LIMITED RESTRICTIONS ON THE POLEMICS OF HIJAB, BURKA, AND NIQAB IN INDONESIA: - Achmad Jauhari Umar (State of Islamic Institute Langsa, 2021)
The niqab and burka are manifestations (forum externum) of freedom of religion and belief (FORB) guaranteed by the UDHR. However, in practice, the niqab and burka, on the other hand, block the application of the FORB. In Europe, the niqab and burka are banned packages that should not be in public. Meanwhile, in Indonesia, after the reforms, the dynamics of the niqab and burka are increasingly diverse. Through the Minister of Religious Affairs, Fachrul Razi, the Ministry of Religious Affairs prohibited the State Civil Apparatus (ASN) women from wearing it while working. On the other hand, there are several regional regulations, such as in Central Lombok. Instead, it is required as a substitute for a medical mask. This paper analyzes the content of the law. It considers the extent to which it can be 'harmonized' so that it does not conflict with Indonesia's aspirations for civil society, non- discrimination, and pluralism. The argument is used as a source of comparison with similar regulations in other countries.